Trends in Health Equity Among Children in the United States, 1997–2018. - Anderson, Nathaniel W.; Zimmerman, Frederick J. (Maternal & Child Health Journal, 2021)
Objectives: Health equity is crucial to population health. To achieve this aim, extensive monitoring efforts beyond traditional disparities research are required. This analysis assesses trends in health equity for children from 1997 to 2018. Methods: Health equity in a given year is calculated using a previously developed measure as the mean weighted departure of individual health from the best achievable level of health. This criterion is defined as the median health of the most socially privileged identifiable group: white, non-Latinx boys in upper-income households. Using more than 20 years of data from the National Health Interview Survey, we apply this methodology to six measures of child health: parent-reported health status, school days missed due to illness or injury in the past year, a strength and difficulties questionnaire score, emotional difficulties, a toddler mental health indicator score, and toddler depression. We separately calculate racial/ethnic and income disparities. Monte Carlo simulation is used to assess whether trends are statistically significant. Results: Health equity among children increased gradually over the past 2 decades, with five of the six measures demonstrating upward trends. Improvements in health equity are stronger among younger children (age 0–3 and 4–7). Unlike previous work examining adults, both types of disparities narrowed over the study period. Conclusions for Practice: Progress on health equity requires accountability to an objective metric. This analysis suggests some improvement over the past two decades, although these gains are under threat from potential decreases in government spending on programs affecting children and the COVID-19 pandemic.